INFLUENCE OF ORGANIZATIONAL CULTURE, EMPLOYEE DEVELOPMENT, AND COMMUNICATION ON RETENTION VIA JOB SATISFACTION - Yusra; Salju; Goso; Rahma; Risma (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study investigates the influence of organizational culture, employee development, and internal communication on employee retention with job satisfaction as a mediating variable. Using a quantitative approach, data was collected from 300 employees in the manufacturing sector in Indonesia through a structured questionnaire. This study uses multiple regression analysis and path analysis to test the relationship between variables. The findings show that organizational culture has a significant effect on job satisfaction, which in turn has a positive effect on employee retention. However, the direct influence of employee development and internal communication on job satisfaction and retention is not statistically significant. Mediation analysis confirms that job satisfaction plays an important role in mediating the relationship between organizational culture and employee retention. These results emphasize the importance of fostering a strong organizational culture and increasing job satisfaction to improve retention rates. The study concludes with recommendations for organizations to focus on creating a supportive culture and implementing strategies that increase job satisfaction as a means to retain top talent.